2013
DOI: 10.1038/ejhg.2013.155
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide estimates of inbreeding in unrelated individuals and their association with cognitive ability

Abstract: The consequence of reduced cognitive ability from inbreeding has long been investigated, mainly restricted to cousin-cousin marriages. Molecular genetic techniques now allow us to test the relationship between increased ancestral inbreeding and cognitive ability in a population of traditionally unrelated individuals. In a representative UK sample of 2329 individuals, we used genome-wide SNP data to estimate the percentage of the genome covered by runs of homozygous SNPs (ROH). This was tested for association w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 31 publications
3
23
2
Order By: Relevance
“…In particular, the estimate for Froh on general cognitive ability was more significant when SNP-by-SNP homozygosity, Fsnp , was removed as a covariate (β = −9.9, t(4852) = −2.92, p = 0.003), whereas Fsnp did not itself predict general cognitive ability (β = −0.1, t(4852) = −0.04, p = 0.97), and suggests that homozygosity at rare variants drove the observed Froh effect. Finally, contrary to a previous report (31), we found no evidence for increased assortative mating or inbreeding at the upper tail of the cognitive ability distribution.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…In particular, the estimate for Froh on general cognitive ability was more significant when SNP-by-SNP homozygosity, Fsnp , was removed as a covariate (β = −9.9, t(4852) = −2.92, p = 0.003), whereas Fsnp did not itself predict general cognitive ability (β = −0.1, t(4852) = −0.04, p = 0.97), and suggests that homozygosity at rare variants drove the observed Froh effect. Finally, contrary to a previous report (31), we found no evidence for increased assortative mating or inbreeding at the upper tail of the cognitive ability distribution.…”
Section: Resultscontrasting
confidence: 99%
“…To date, a number of studies have examined the effect of Froh burden and individual ROH regions on case/control and quantitative phenotypes, with early studies showing mixed results (30), including a non-significant Froh -cognitive ability relationship among individuals of European ancestry (N=2329) (31). Given the low variation in Froh among outbred samples, it is likely that these studies were underpowered (29).…”
Section: Introductionmentioning
confidence: 99%
“…In the classical twin design, dominance variation (making dizygotic twins more dissimilar than half the similarity of monozygotic twins) can be obscured by shared environment effects (making dizygotic twins more similar). There is some evidence from other approaches that dominance only plays a minor role in intelligence differences [80][81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on ROH and cognition in different strata of the general population have shown mixed results, with moderate effect sizes [6][7][8] . While two studies 6,8 suggest that inbreeding depression may decrease adult intelligence, divergent results by Power et al 7 could be explained in view of three evidences. First, assortative mating has recently been highlighted as an important factor underlying psychiatric and behavioral phenotypes [9][10][11][12] , in line with specific findings showing assortative mating in relation to cognitive ability published in the late 20 th century 13,14 genetic effects on brain structure and function, but the evidence of associations between genetic risk for schizophrenia and brain features is scarce, with some studies reporting no overlap between schizophrenia PGRS and subcortical phenotypes derived from magnetic resonance imaging (MRI) 21 ,…”
mentioning
confidence: 99%